Need Analysis on English Language Use by Hotel Staffs in Bandung - Alfian Azhar Yamin (Journal of English Language Teaching and English Linguistics, 2021)
Need analysis is one of the important factors in developing ESP curriculum. There are three aspects in analyzing the target needs: Necessities, Lacks, and Wants. Need analysis in this study was conducted in order to develop ESP syllabus in English for Hotel students. This research aimed to discover the needs of english language skill in the specific field, focused on analyzing the english language needs of hotel staffs in Bandung. As a quantitative study, a questionnaire was addressed to 27 hotel staffs in Bandung to find the difficulties they encounter when using English language and the specific needs to develop their english language skill. The findings of this study showed that speaking is the most important skill that Hotel Staffs need to learn based on the findings of this study. Moreover, the speaking skill for giving information about facilities and services around hotel is highly needed followed by handling complaint.